Serum albumin and risk of venous thromboembolism. - Folsom, Aaron R; Lutsey, Pamela L; Heckbert, Susan R; Cushman, Mary (Thromb Haemost, 2010)
The incidence of venous thromboembolism (VTE) is increased in patients with albuminuria. However, whether a low serum albumin concentration is associated with increased risk of VTE has been a matter of controversy. We determined the association of serum albumin with VTE incidence in two large, prospective, population-based cohorts: the Atherosclerosis Risk in Communities (ARIC) Study (n = 15,300) and the Cardiovascular Health Study (CHS) (n = 5,400). Validated VTE occurrence (n = 462 in ARIC and n = 174 in CHS) was ascertained during follow-up. In both studies, after adjustment for age, sex, race, use of hormone replacement therapy, estimated glomerular filtration rate, history of cancer, and diabetes, serum albumin tended to be associated inversely with VTE. The adjusted hazard ratio per standard deviation lower albumin was 1.18 (95% confidence interval [CI] = 1.08, 1.31) in ARIC and 1.10 (95% CI = 0.94, 1.29) in CHS. The hazard ratio for albumin below (vs. above) the fifth percentile was 1.28 (95% CI = 0.90, 1.84) in ARIC and 1.80 (95% CI = 1.11, 2.93) in CHS. In conclusion, low serum albumin was a modest marker of increased VTE risk. The observed association likely does not reflect cause and effect, but rather that low serum albumin reflects a hyperinflammatory or hypercoagulable state. Whether this association has clinical relevance warrants further study.
Keywords: Aged; Biomarkers; Female; Follow-Up Studies; Humans; Incidence; Male; Middle Aged; Risk Factors; Serum Albumin; United States; Venous Thromboembolism

A genome-wide association study of aging. - Walter, Stefan; Atzmon, Gil; Demerath, Ellen W; Garcia, Melissa E; Kaplan, Robert C; Kumari, Meena; Lunetta, Kathryn L; Milaneschi, Yuri; Tanaka, Toshiko; Tranah, Gregory J; Völker, Uwe; Yu, Lei; et al. (Neurobiol Aging, 2011)
Human longevity and healthy aging show moderate heritability (20%-50%). We conducted a meta-analysis of genome-wide association studies from 9 studies from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium for 2 outcomes: (1) all-cause mortality, and (2) survival free of major disease or death. No single nucleotide polymorphism (SNP) was a genome-wide significant predictor of either outcome (p < 5 × 10(-8)). We found 14 independent SNPs that predicted risk of death, and 8 SNPs that predicted event-free survival (p < 10(-5)). These SNPs are in or near genes that are highly expressed in the brain (HECW2, HIP1, BIN2, GRIA1), genes involved in neural development and function (KCNQ4, LMO4, GRIA1, NETO1) and autophagy (ATG4C), and genes that are associated with risk of various diseases including cancer and Alzheimer's disease. In addition to considerable overlap between the traits, pathway and network analysis corroborated these findings. These findings indicate that variation in genes involved in neurological processes may be an important factor in regulating aging free of major disease and achieving longevity.
Keywords: Aging; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Longevity

Longer legs are associated with greater risk of incident venous thromboembolism independent of total body height. The Longitudinal Study of Thromboembolism Etiology (LITE). - Lutsey, Pamela L; Cushman, Mary; Heckbert, Susan R; Tang, Weihong; Folsom, Aaron R (Thromb Haemost, 2011)
Several studies have reported that taller individuals are at greater risk of venous thromboembolism (VTE). We hypothesised that longer leg length would be positively associated with incident VTE, and would explain the height association. LITE ascertained VTE in a prospective population-based sample of 21,860 individuals aged 45 and older. Leg length was measured as standing height minus torso length. Cox regression models were adjusted for age, race, sex, waist circumference, diabetes, and factor VIII. To evaluate whether leg length was associated with VTE risk independent of height, we standardised leg length and height per 1 standard deviation (SD), and then included them simultaneously in Cox regression models. A total of 641 incident VTE cases accrued over a median follow-up of 16 years. Participants in the highest quintile of leg length were at 59% (95% CI: 22%-108%) greater risk of VTE, relative to the lowest quintile. For height, risk was 45% (12%-88%) greater for those in the highest quintile, compared to the lowest. When leg length and height were modelled simultaneously leg length remained associated with VTE risk (HR per 1 SD: 1.21 (1.04-1.40) while height was unrelated (HR per 1 SD: 1.00 (0.86-1.16). To conclude, participants with longer legs were at greater risk of incident VTE, and leg length explained the relation of height to VTE. It remains to be established whether this finding is due to greater venous surface area, a larger number of venous valves, or greater hydrostatic pressure among individuals with longer legs.
Keywords: Adult; Aged; Anthropometry; Body Height; Female; Follow-Up Studies; Humans; Leg; Male; Middle Aged; Population Groups; Prospective Studies; Risk Factors; United States; Venous Thromboembolism

Association of mild to moderate chronic kidney disease with venous thromboembolism: pooled analysis of five prospective general population cohorts. - Mahmoodi, Bakhtawar K; Gansevoort, Ron T; Næss, Inger Anne; Lutsey, Pamela L; Brækkan, Sigrid K; Veeger, Nic J G M; Brodin, Ellen E; Meijer, Karina; Sang, Yingying; Matsushita, Kunihiro; Hallan, Stein I; Hammerstrøm, Jens; et al. (Circulation, 2012)
BACKGROUND: Recent findings suggest that chronic kidney disease (CKD) may be associated with an increased risk of venous thromboembolism (VTE). Given the high prevalence of mild-to-moderate CKD in the general population, in depth analysis of this association is warranted. METHODS AND RESULTS: We pooled individual participant data from 5 community-based cohorts from Europe (second Nord-Trøndelag Health Study [HUNT2], Prevention of Renal and Vascular End-stage Disease [PREVEND], and the Tromsø study) and the United States (Atherosclerosis Risks in Communities [ARIC] and Cardiovascular Health Study [CHS]) to assess the association of estimated glomerular filtration rate (eGFR), albuminuria, and CKD with objectively verified VTE. To estimate adjusted hazard ratios for VTE, categorical and continuous spline models were fit by using Cox regression with shared-frailty or random-effect meta-analysis. A total of 1178 VTE events occurred over 599 453 person-years follow-up. Relative to eGFR 100 mL/min per 1.73 m(2), hazard ratios for VTE were 1.29 (95% confidence interval, 1.04-1.59) for eGFR 75, 1.31 (1.00-1.71) for eGFR 60, 1.82 (1.27-2.60) for eGFR 45, and 1.95 (1.26-3.01) for eGFR 30 mL/min per 1.73 m(2). In comparison with an albumin-to-creatinine ratio (ACR) of 5.0 mg/g, the hazard ratios for VTE were 1.34 (1.04-1.72) for ACR 30 mg/g, 1.60 (1.08-2.36) for ACR 300 mg/g, and 1.92 (1.19-3.09) for ACR 1000 mg/g. There was no interaction between clinical categories of eGFR and ACR (P=0.20). The adjusted hazard ratio for CKD, defined as eGFR <60 mL/min per 1.73 m(2) or albuminuria ≥30 mg/g, (versus no CKD) was 1.54 (95% confidence interval, 1.15-2.06). Associations were consistent in subgroups according to age, sex, and comorbidities, and for unprovoked versus provoked VTE, as well. CONCLUSIONS: Both eGFR and ACR are independently associated with increased risk of VTE in the general population, even across the normal eGFR and ACR ranges.
Keywords: Aged; Cohort Studies; Europe; Female; Humans; Incidence; Male; Middle Aged; Prevalence; Renal Insufficiency, Chronic; Risk Factors; Severity of Illness Index; Venous Thromboembolism

Racial and regional differences in venous thromboembolism in the United States in 3 cohorts. - Zakai, Neil A; McClure, Leslie A; Judd, Suzanne E; Safford, Monika M; Folsom, Aaron R; Lutsey, Pamela L; Cushman, Mary (Circulation, 2014)
BACKGROUND: Blacks are thought to have a higher risk of venous thromboembolism (VTE) than whites. However, prior studies are limited to administrative databases that lack specific information on VTE risk factors or have limited geographic scope. METHODS AND RESULTS: We ascertained VTE from 3 prospective studies: the Atherosclerosis Risk in Communities Study (ARIC), the Cardiovascular Health Study (CHS), and the Reasons for Geographic and Racial Differences in Stroke study (REGARDS). We tested the association of race with VTE using Cox proportional hazard models adjusted for VTE risk factors. Over 438 090 person-years, 916 incident VTE events (302 in blacks) occurred in 51 149 individuals (17 318 blacks) who were followed up. In risk factor-adjusted models, blacks had a higher rate of VTE than whites in the CHS (hazard ratio, 1.81; 95% confidence interval, 1.20-2.73) but not ARIC (hazard ratio, 1.21; 95% confidence interval, 0.96-1.54). In REGARDS, there was a significant region-by-race interaction (P=0.01): Blacks in the Southeast had a significantly higher rate of VTE than blacks in the rest of the United States (hazard ratio, 1.63; 95% confidence interval, 1.08-2.48) that was not seen in whites (hazard ratio, 0.83; 95% confidence interval, 0.61-1.14). CONCLUSIONS: The association of race with VTE differed in each cohort, which may reflect the different time periods of the studies or different regional rates of VTE. Further studies of environmental and genetic risk factors for VTE are needed to determine which underlie racial and perhaps regional differences in VTE.
Keywords: African Continental Ancestry Group; Aged; Cohort Studies; European Continental Ancestry Group; Female; Humans; Longitudinal Studies; Male; Middle Aged; Prevalence; Proportional Hazards Models; Prospective Studies; Residence Characteristics; Risk Factors; United States; Venous Thromboembolism

Troponin T, NT-proBNP, and venous thromboembolism: the Longitudinal Investigation of Thromboembolism Etiology (LITE). - Folsom, Aaron R; Lutsey, Pamela L; Nambi, Vijay; deFilippi, Christopher R; Heckbert, Susan R; Cushman, Mary; Ballantyne, Christie M (Vasc Med, 2014)
Increased levels of plasma troponins and natriuretic peptides are markers of cardiac dysfunction associated with increased risk of cardiovascular disease. Little information exists on cardiac dysfunction and occurrence of venous thromboembolism (VTE). In two prospective epidemiological cohorts, we tested the hypothesis that high-sensitivity troponin T (TnT) and N-terminal pro B-type natriuretic peptide (NT-proBNP) are associated positively with VTE occurrence. The Atherosclerosis Risk in Communities (ARIC) study and the Cardiovascular Health Study (CHS) measured plasma TnT and NT-proBNP in 13,719 men or women with no history of venous thrombosis, coronary heart disease, or heart failure and followed them for approximately 10 years for VTE occurrence (n = 348 VTEs). In both ARIC and CHS, TnT was associated positively with incidence of total VTE and provoked VTE, but not with unprovoked VTE: age, race, and sex-adjusted hazard ratios for total VTE in the pooled analysis were 1.00, 0.85, 1.36, 1.51, and 1.98 (p-trend <0.0001) across five categories of TnT. In contrast, the association of NT-proBNP with VTE was positive in ARIC (hazard ratios approximately 2.5-fold for the highest versus lowest NT-proBNP quintiles), but non-existent in CHS.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Biomarkers; Female; Heart Failure; Humans; Incidence; Longitudinal Studies; Male; Middle Aged; Natriuretic Peptide, Brain; Peptide Fragments; Prospective Studies; Risk Factors; Troponin T; Venous Thromboembolism

Diabetes mellitus and venous thromboembolism: A systematic review and meta-analysis. - Bell, Elizabeth J; Folsom, Aaron R; Lutsey, Pamela L; Selvin, Elizabeth; Zakai, Neil A; Cushman, Mary; Alonso, Alvaro (Diabetes Res Clin Pract, 2016)
UNLABELLED: Diabetes mellitus (DM) may be a risk factor for venous thromboembolism (VTE) but results are inconsistent. AIM: We conducted a systematic review and meta-analysis of epidemiologic studies to quantify the association between DM and VTE. METHODS AND RESULTS: We included studies identified in PubMed, Web of Science, and CINAHL through 07/31/2014. We identified 19 studies that met our selection criteria. We pooled RRs using a random-effects model: the pooled RR for the association of DM with VTE was 1.10 (95% CI: 0.94-1.29). Between-study heterogeneity was explored with a forest plot, funnel plot, meta-regression, and a stratified analysis. Between-study heterogeneity was observed and not explained by study design, method of DM assessment, or degree of adjustment for confounding. Sensitivity analyses omitted one study at a time to assess the influence of any single study on the pooled estimate. These analyses indicated that one large study was highly influential; when this study was excluded, the pooled estimate increased and just reached statistical significance: 1.16 (95% CI: 1.01-1.34). CONCLUSIONS: This meta-analysis suggests either no association or a modest positive one between DM and VTE in the general population. DM is unlikely to play a major role in VTE development.

Genetic Variants Associated with Circulating Parathyroid Hormone. - Robinson-Cohen, Cassianne; Lutsey, Pamela L; Kleber, Marcus E; Nielson, Carrie M; Mitchell, Braxton D; Bis, Joshua C; Eny, Karen M; Portas, Laura; Eriksson, Joel; Lorentzon, Mattias; Koller, Daniel L; Milaneschi, Yuri; et al. (J Am Soc Nephrol, 2016)
Parathyroid hormone (PTH) is a primary calcium regulatory hormone. Elevated serum PTH concentrations in primary and secondary hyperparathyroidism have been associated with bone disease, hypertension, and in some studies, cardiovascular mortality. Genetic causes of variation in circulating PTH concentrations are incompletely understood. We performed a genome-wide association study of serum PTH concentrations among 29,155 participants of European ancestry from 13 cohort studies (n=22,653 and n=6502 in discovery and replication analyses, respectively). We evaluated the association of single nucleotide polymorphisms (SNPs) with natural log-transformed PTH concentration adjusted for age, sex, season, study site, and principal components of ancestry. We discovered associations of SNPs from five independent regions with serum PTH concentration, including the strongest association with rs6127099 upstream of CYP24A1 (P=4.2 × 10(-53)), a gene that encodes the primary catabolic enzyme for 1,25-dihydroxyvitamin D and 25-dihydroxyvitamin D. Each additional copy of the minor allele at this SNP associated with 7% higher serum PTH concentration. The other SNPs associated with serum PTH concentration included rs4074995 within RGS14 (P=6.6 × 10(-17)), rs219779 adjacent to CLDN14 (P=3.5 × 10(-16)), rs4443100 near RTDR1 (P=8.7 × 10(-9)), and rs73186030 near CASR (P=4.8 × 10(-8)). Of these five SNPs, rs6127099, rs4074995, and rs219779 replicated. Thus, common genetic variants located near genes involved in vitamin D metabolism and calcium and renal phosphate transport associated with differences in circulating PTH concentrations. Future studies could identify the causal variants at these loci, and the clinical and functional relevance of these variants should be pursued.

Lifetime Risk of Venous Thromboembolism in Two Cohort Studies. - Bell, Elizabeth J; Lutsey, Pamela L; Basu, Saonli; Cushman, Mary; Heckbert, Susan R; Lloyd-Jones, Donald M; Folsom, Aaron R (Am J Med, 2016)
BACKGROUND: Greater public awareness of venous thromboembolism may be an important next step for optimizing venous thromboembolism prevention and treatment. "Lifetime risk" is an easily interpretable way of presenting risk information. Therefore, we sought to calculate the lifetime risk of venous thromboembolism (deep vein thrombosis or pulmonary embolism) using data from 2 large, prospective cohort studies: the Cardiovascular Health Study (CHS) and the Atherosclerosis Risk in Communities (ARIC) study. METHODS: We followed participants aged 45-64 years in ARIC (n = 14,185) and ≥65 in CHS (n = 5414) at baseline visits (1987-1989 in ARIC, 1989-1990 and 1992-1993 in CHS) for incident venous thromboembolism (n = 728 in ARIC through 2011 and n = 172 in CHS through 2001). We estimated lifetime risks and 95% confidence intervals of incident venous thromboembolism using a modified Kaplan-Meier method, accounting for the competing risk of death from other causes. RESULTS: At age 45 years, the remaining lifetime risk of venous thromboembolism in ARIC was 8.1% (95% confidence interval, 7.1-8.7). High-risk groups were African Americans (11.5% lifetime risk), those with obesity (10.9%), heterozygous for the factor V Leiden (17.1%), or with sickle cell trait or disease (18.2%). Lifetime risk estimates differed by cohort; these differences were explained by differences in time period of venous thromboembolism ascertainment. CONCLUSIONS: At least 1 in 12 middle-aged adults will develop venous thromboembolism in their remaining lifetime. This estimate of lifetime risk may be useful to promote awareness of venous thromboembolism and guide decisions at both clinical and policy levels.
Keywords: African Continental Ancestry Group; Aged; Anemia, Sickle Cell; Cohort Studies; Factor V; Follow-Up Studies; Heterozygote; Humans; Kaplan-Meier Estimate; Middle Aged; Obesity; Risk; Sickle Cell Trait; United States; Venous Thromboembolism

Orthostatic Hypotension and Risk of Venous Thromboembolism in 2 Cohort Studies. - Bell, Elizabeth J; Agarwal, Sunil K; Cushman, Mary; Heckbert, Susan R; Lutsey, Pamela L; Folsom, Aaron R (Am J Hypertens, 2016)
BACKGROUND: Although venous stasis is a risk factor for venous thromboembolism (VTE) and orthostatic hypotension (OH) can cause venous stasis, to our knowledge no study has examined the relationship between OH and VTE risk. We sought to quantify the association between OH and VTE (deep vein thrombosis or pulmonary embolism) using data from 2 large, prospective cohort studies: the Cardiovascular Health Study (CHS) and the Atherosclerosis Risk in Communities (ARIC) Study. We hypothesized that OH was positively associated with incident VTE. METHODS: We measured OH-defined as a drop in systolic blood pressure (SBP) of at least 20 mm Hg or diastolic blood pressure (DBP) of at least 10 mm Hg within 3 minutes of standing-in participants aged 45-64 years in ARIC (n = 12,480) and ≥65 years in CHS (n = 5,027) at baseline visits (1987-1989 in ARIC; 1989-1990 and 1992-1993 in CHS), and followed participants for incident VTE (n = 568 in ARIC through 2011 and n = 148 in CHS through 2001). We calculated adjusted hazard ratios (HRs) and their 95% confidence intervals (CIs) for incident VTE in relation to OH status. RESULTS: In CHS, there was a positive association between OH status and incident VTE (HR for VTE = 1.74 (95% CI: 1.20-2.51)). In contrast, there was no association between OH and VTE in the ARIC study (HR for VTE = 0.97 (95% CI: 0.70-1.33)). CONCLUSIONS: Community-dwelling older adults with OH had a moderately increased risk of VTE. These results were not seen in a population-based middle-aged cohort.

Genetic Variants Associated with Circulating Fibroblast Growth Factor 23. - Robinson-Cohen, Cassianne; Bartz, Traci M; Lai, Dongbing; Ikizler, T Alp; Peacock, Munro; Imel, Erik A; Michos, Erin D; Foroud, Tatiana M; Åkesson, Kristina; Taylor, Kent D; Malmgren, Linnea; Matsushita, Kunihiro; et al. (J Am Soc Nephrol, 2018)
BACKGROUND: Fibroblast growth factor 23 (FGF23), a bone-derived hormone that regulates phosphorus and vitamin D metabolism, contributes to the pathogenesis of mineral and bone disorders in CKD and is an emerging cardiovascular risk factor. Central elements of FGF23 regulation remain incompletely understood; genetic variation may help explain interindividual differences. METHODS: We performed a meta-analysis of genome-wide association studies of circulating FGF23 concentrations among 16,624 participants of European ancestry from seven cohort studies, excluding participants with eGFR<30 ml/min per 1.73 m to focus on FGF23 under normal conditions. We evaluated the association of single-nucleotide polymorphisms (SNPs) with natural log-transformed FGF23 concentration, adjusted for age, sex, study site, and principal components of ancestry. A second model additionally adjusted for BMI and eGFR. RESULTS: We discovered 154 SNPs from five independent regions associated with FGF23 concentration. The SNP with the strongest association, rs17216707 (=3.0×10), lies upstream of , which encodes the primary catabolic enzyme for 1,25-dihydroxyvitamin D and 25-hydroxyvitamin D. Each additional copy of the T allele at this locus is associated with 5% higher FGF23 concentration. Another locus strongly associated with variations in FGF23 concentration is rs11741640, within and upstream of (a gene involved in renal phosphate transport). Additional adjustment for BMI and eGFR did not materially alter the magnitude of these associations. Another top locus (within , the ABO blood group transferase gene) was no longer statistically significant at the genome-wide level. CONCLUSIONS: Common genetic variants located near genes involved in vitamin D metabolism and renal phosphate transport are associated with differences in circulating FGF23 concentrations.

Genome-wide association study in 79,366 European-ancestry individuals informs the genetic architecture of 25-hydroxyvitamin D levels. - Jiang, Xia; O'Reilly, Paul F; Aschard, Hugues; Hsu, Yi-Hsiang; Richards, J Brent; Dupuis, Josée; Ingelsson, Erik; Karasik, David; Pilz, Stefan; Berry, Diane; Kestenbaum, Bryan; Zheng, Jusheng; et al. (Nat Commun, 2018)
Vitamin D is a steroid hormone precursor that is associated with a range of human traits and diseases. Previous GWAS of serum 25-hydroxyvitamin D concentrations have identified four genome-wide significant loci (GC, NADSYN1/DHCR7, CYP2R1, CYP24A1). In this study, we expand the previous SUNLIGHT Consortium GWAS discovery sample size from 16,125 to 79,366 (all European descent). This larger GWAS yields two additional loci harboring genome-wide significant variants (P = 4.7×10 at rs8018720 in SEC23A, and P = 1.9×10 at rs10745742 in AMDHD1). The overall estimate of heritability of 25-hydroxyvitamin D serum concentrations attributable to GWAS common SNPs is 7.5%, with statistically significant loci explaining 38% of this total. Further investigation identifies signal enrichment in immune and hematopoietic tissues, and clustering with autoimmune diseases in cell-type-specific analysis. Larger studies are required to identify additional common SNPs, and to explore the role of rare or structural variants and gene-gene interactions in the heritability of circulating 25-hydroxyvitamin D levels.

Meta-analysis across Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium provides evidence for an association of serum vitamin D with pulmonary function. - Xu, Jiayi; Bartz, Traci M; Chittoor, Geetha; Eiriksdottir, Gudny; Manichaikul, Ani W; Sun, Fangui; Terzikhan, Natalie; Zhou, Xia; Booth, Sarah L; Brusselle, Guy G; de Boer, Ian H; Fornage, Myriam; et al. (Br J Nutr, 2018)
The role that vitamin D plays in pulmonary function remains uncertain. Epidemiological studies reported mixed findings for serum 25-hydroxyvitamin D (25(OH)D)-pulmonary function association. We conducted the largest cross-sectional meta-analysis of the 25(OH)D-pulmonary function association to date, based on nine European ancestry (EA) cohorts (n 22 838) and five African ancestry (AA) cohorts (n 4290) in the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium. Data were analysed using linear models by cohort and ancestry. Effect modification by smoking status (current/former/never) was tested. Results were combined using fixed-effects meta-analysis. Mean serum 25(OH)D was 68 (sd 29) nmol/l for EA and 49 (sd 21) nmol/l for AA. For each 1 nmol/l higher 25(OH)D, forced expiratory volume in the 1st second (FEV1) was higher by 1·1 ml in EA (95 % CI 0·9, 1·3; P<0·0001) and 1·8 ml (95 % CI 1·1, 2·5; P<0·0001) in AA (P race difference=0·06), and forced vital capacity (FVC) was higher by 1·3 ml in EA (95 % CI 1·0, 1·6; P<0·0001) and 1·5 ml (95 % CI 0·8, 2·3; P=0·0001) in AA (P race difference=0·56). Among EA, the 25(OH)D-FVC association was stronger in smokers: per 1 nmol/l higher 25(OH)D, FVC was higher by 1·7 ml (95 % CI 1·1, 2·3) for current smokers and 1·7 ml (95 % CI 1·2, 2·1) for former smokers, compared with 0·8 ml (95 % CI 0·4, 1·2) for never smokers. In summary, the 25(OH)D associations with FEV1 and FVC were positive in both ancestries. In EA, a stronger association was observed for smokers compared with never smokers, which supports the importance of vitamin D in vulnerable populations.

Trans-ethnic Evaluation Identifies Novel Low Frequency Loci Associated with 25-Hydroxyvitamin D Concentrations. - Hong, Jaeyoung; Hatchell, Kathryn E; Bradfield, Jonathan P; Andrew, Bjonnes; Alessandra, Chesi; Chao-Qiang, Lai; Langefeld, Carl D; Lu, Lingyi; Lu, Yingchang; Lutsey, Pamela L; Musani, Solomon K; Nalls, Mike A; et al. (J Clin Endocrinol Metab, 2018)
Context: Vitamin D inadequacy is common in the adult population of the United States. While the genetic determinants underlying vitamin D inadequacy have been studied in people of European ancestry, less is known in Hispanic or African ancestry populations. Objective: The TRANSCEN-D (TRANS-ethniC Evaluation of vitamiN D GWAS) consortium was assembled to replicate genetic associations with 25-hydroxyvitamin D (25(OH)D) concentrations from the meta-analyses of European ancestry (SUNLIGHT) and to identify novel genetic variants related to vitamin D concentrations in African and Hispanic ancestries. Design: Ancestry-specific (Hispanic and African) and trans-ethnic (Hispanic, African and European) meta-analyses were performed using the METAL software. Patients or Other Participants: In total, 8,541 African-American and 3,485 Hispanic-American (from North America) participants from twelve cohorts, and 16,124 European participants from SUNLIGHT were included in the study. Main Outcome Measure(s): Blood concentrations of 25(OH)D were measured for all participants. Results: Ancestry-specific analyses in African and Hispanic Americans replicated SNPs in GC (2 and 4 SNPs, respectively). A potentially novel SNP (rs79666294) near the KIF4B gene was identified in the African-American cohort. Trans-ethnic evaluation replicated GC and DHCR7 region SNPs. Additionally, the trans-ethnic analyses revealed novel SNPs rs719700 and rs1410656 near the ANO6/ARID2 and HTR2A genes, respectively. Conclusions: Ancestry-specific and trans-ethnic GWAS of 25(OH)D confirmed findings in GC and DHCR7 for African and Hispanic American samples and revealed novel findings near KIF4B, ANO6/ARID2, and HTR2A. The biological mechanisms that link these regions with 25(OH)D metabolism require further investigation.

Sequencing Analysis at 8p23 Identifies Multiple Rare Variants in DLC1 Associated with Sleep-Related Oxyhemoglobin Saturation Level. - Liang, Jingjing; Cade, Brian E; He, Karen Y; Wang, Heming; Lee, Jiwon; Sofer, Tamar; Williams, Stephanie; Li, Ruitong; Chen, Han; Gottlieb, Daniel J; Evans, Daniel S; Guo, Xiuqing; et al. (Am J Hum Genet, 2019)
Average arterial oxyhemoglobin saturation during sleep (AvSpOS) is a clinically relevant measure of physiological stress associated with sleep-disordered breathing, and this measure predicts incident cardiovascular disease and mortality. Using high-depth whole-genome sequencing data from the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) project and focusing on genes with linkage evidence on chromosome 8p23, we observed that six coding and 51 noncoding variants in a gene that encodes the GTPase-activating protein (DLC1) are significantly associated with AvSpOS and replicated in independent subjects. The combined DLC1 association evidence of discovery and replication cohorts reaches genome-wide significance in European Americans (p = 7.9 × 10). A risk score for these variants, built on an independent dataset, explains 0.97% of the AvSpOS variation and contributes to the linkage evidence. The 51 noncoding variants are enriched in regulatory features in a human lung fibroblast cell line and contribute to DLC1 expression variation. Mendelian randomization analysis using these variants indicates a significant causal effect of DLC1 expression in fibroblasts on AvSpOS. Multiple sources of information, including genetic variants, gene expression, and methylation, consistently suggest that DLC1 is a gene associated with AvSpOS.

Cross-Ancestry Investigation of Venous Thromboembolism Genomic Predictors. - Thibord, Florian; Klarin, Derek; Brody, Jennifer A; Chen, Ming-Huei; Levin, Michael G; Chasman, Daniel I; Goode, Ellen L; Hveem, Kristian; Teder-Laving, Maris; Martinez-Perez, Angel; Aïssi, Dylan; Daian-Bacq, Delphine; et al. (Circulation, 2022)
BACKGROUND: Venous thromboembolism (VTE) is a life-threatening vascular event with environmental and genetic determinants. Recent VTE genome-wide association studies (GWAS) meta-analyses involved nearly 30 000 VTE cases and identified up to 40 genetic loci associated with VTE risk, including loci not previously suspected to play a role in hemostasis. The aim of our research was to expand discovery of new genetic loci associated with VTE by using cross-ancestry genomic resources. METHODS: We present new cross-ancestry meta-analyzed GWAS results involving up to 81 669 VTE cases from 30 studies, with replication of novel loci in independent populations and loci characterization through in silico genomic interrogations. RESULTS: In our genetic discovery effort that included 55 330 participants with VTE (47 822 European, 6320 African, and 1188 Hispanic ancestry), we identified 48 novel associations, of which 34 were replicated after correction for multiple testing. In our combined discovery-replication analysis (81 669 VTE participants) and ancestry-stratified meta-analyses (European, African, and Hispanic), we identified another 44 novel associations, which are new candidate VTE-associated loci requiring replication. In total, across all GWAS meta-analyses, we identified 135 independent genomic loci significantly associated with VTE risk. A genetic risk score of the significantly associated loci in Europeans identified a 6-fold increase in risk for those in the top 1% of scores compared with those with average scores. We also identified 31 novel transcript associations in transcriptome-wide association studies and 8 novel candidate genes with protein quantitative-trait locus Mendelian randomization analyses. In silico interrogations of hemostasis and hematology traits and a large phenome-wide association analysis of the 135 GWAS loci provided insights to biological pathways contributing to VTE, with some loci contributing to VTE through well-characterized coagulation pathways and others providing new data on the role of hematology traits, particularly platelet function. Many of the replicated loci are outside of known or currently hypothesized pathways to thrombosis. CONCLUSIONS: Our cross-ancestry GWAS meta-analyses identified new loci associated with VTE. These findings highlight new pathways to thrombosis and provide novel molecules that may be useful in the development of improved antithrombosis treatments.
Keywords: Genetic Predisposition to Disease; Genome-Wide Association Study; Genomics; Humans; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Thrombosis; Venous Thromboembolism

Targeted Genome Sequencing Identifies Multiple Rare Variants in Caveolin-1 Associated with Obstructive Sleep Apnea. - Liang, Jingjing; Wang, Heming; Cade, Brian E; Kurniansyah, Nuzulul; He, Karen Y; Lee, Jiwon; Sands, Scott A; Brody, Jennifer; Chen, Han; Gottlieb, Daniel J; Evans, Daniel S; Guo, Xiuqing; et al. (Am J Respir Crit Care Med, 2022)
INTRODUCTION: Obstructive sleep apnea (OSA) is a common disorder associated with increased risk for cardiovascular disease, diabetes, and premature mortality. There is strong clinical and epi-demiologic evidence supporting the importance of genetic factors influencing OSA, but limited data implicating specific genes. METHODS: Leveraging high depth genomic sequencing data from the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) program and imputed genotype data from multiple population-based studies, we performed linkage analysis in the Cleve-land Family Study (CFS) followed by multi-stage gene-based association analyses in independent cohorts to search for rare variants contributing to OSA severity as assessed by the apnea-hypopnea index (AHI) in a total of 7,708 individuals of European ancestry. RESULTS: Linkage analysis in CFS identified a suggestive linkage peak on chromosome 7q31 (LOD=2.31). Gene-based analysis identified 21 non-coding rare variants in Caveolin-1 (CAV1) associated with lower AHI after accounting for multiple comparisons (p=7.4×10-8). These non-coding variants together significantly contributed to the linkage evidence (p<10-3). Follow-up anal-ysis revealed significant associations between these variants and increased CAV1 expression, and increased CAV1 expression in peripheral monocytes was associated with lower AHI (p=0.024) and higher minimum overnight oxygen saturation (p=0.007). CONCLUSION: Rare variants in CAV1, a membrane scaffolding protein essential in multiple cellular and metabolic functions, are associated with higher CAV1 gene expression and lower OSA severity, suggesting a novel target for modulating OSA severity.

Association of Severe Hypercholesterolemia and Familial Hypercholesterolemia Genotype With Risk of Coronary Heart Disease. - Zhang, Yiyi; Dron, Jacqueline S; Bellows, Brandon K; Khera, Amit V; Liu, Junxiu; Balte, Pallavi P; Oelsner, Elizabeth C; Amr, Sami Samir; Lebo, Matthew S; Nagy, Anna; Peloso, Gina M; Natarajan, Pradeep; et al. (Circulation, 2023)
Keywords: Coronary Disease; Genotype; Humans; Hypercholesterolemia; Hyperlipoproteinemia Type II

Sleep Architecture, Obstructive Sleep Apnea, and Cognitive Function in Adults. - Pase, Matthew P; Harrison, Stephanie; Misialek, Jeffrey R; Kline, Christopher E; Cavuoto, Marina; Baril, Andree-Ann; Yiallourou, Stephanie; Bisson, Alycia; Himali, Dibya; Leng, Yue; Yang, Qiong; Seshadri, Sudha; et al. (JAMA Netw Open, 2023)
IMPORTANCE: Good sleep is essential for health, yet associations between sleep and dementia risk remain incompletely understood. The Sleep and Dementia Consortium was established to study associations between polysomnography (PSG)-derived sleep and the risk of dementia and related cognitive and brain magnetic resonance imaging endophenotypes. OBJECTIVE: To investigate association of sleep architecture and obstructive sleep apnea (OSA) with cognitive function in the Sleep and Dementia Consortium. DESIGN, SETTING, AND PARTICIPANTS: The Sleep and Dementia Consortium curated data from 5 population-based cohorts across the US with methodologically consistent, overnight, home-based type II PSG and neuropsychological assessments over 5 years of follow-up: the Atherosclerosis Risk in Communities study, Cardiovascular Health Study, Framingham Heart Study (FHS), Osteoporotic Fractures in Men Study, and Study of Osteoporotic Fractures. Sleep metrics were harmonized centrally and then distributed to participating cohorts for cohort-specific analysis using linear regression; study-level estimates were pooled in random effects meta-analyses. Results were adjusted for demographic variables, the time between PSG and neuropsychological assessment (0-5 years), body mass index, antidepressant use, and sedative use. There were 5946 participants included in the pooled analyses without stroke or dementia. Data were analyzed from March 2020 to June 2023. EXPOSURES: Measures of sleep architecture and OSA derived from in-home PSG. MAIN OUTCOMES AND MEASURES: The main outcomes were global cognitive composite z scores derived from principal component analysis, with cognitive domains investigated as secondary outcomes. Higher scores indicated better performance. RESULTS: Across cohorts, 5946 adults (1875 females [31.5%]; mean age range, 58-89 years) were included. The median (IQR) wake after sleep onset time ranged from 44 (27-73) to 101 (66-147) minutes, and the prevalence of moderate to severe OSA ranged from 16.9% to 28.9%. Across cohorts, higher sleep maintenance efficiency (pooled β per 1% increase, 0.08; 95% CI, 0.03 to 0.14; P < .01) and lower wake after sleep onset (pooled β per 1-min increase, -0.07; 95% CI, -0.13 to -0.01 per 1-min increase; P = .02) were associated with better global cognition. Mild to severe OSA (apnea-hypopnea index [AHI] ≥5) was associated with poorer global cognition (pooled β, -0.06; 95% CI, -0.11 to -0.01; P = .01) vs AHI less than 5; comparable results were found for moderate to severe OSA (pooled β, -0.06; 95% CI, -0.11 to -0.01; P = .02) vs AHI less than 5. Differences in sleep stages were not associated with cognition. CONCLUSIONS AND RELEVANCE: This study found that better sleep consolidation and the absence of OSA were associated with better global cognition over 5 years of follow-up. These findings suggest that the role of interventions to improve sleep for maintaining cognitive function requires investigation.

Familial Hypercholesterolemia Variant and Cardiovascular Risk in Individuals With Elevated Cholesterol. - Zhang, Yiyi; Dron, Jacqueline S; Bellows, Brandon K; Khera, Amit V; Liu, Junxiu; Balte, Pallavi P; Oelsner, Elizabeth C; Amr, Sami Samir; Lebo, Matthew S; Nagy, Anna; Peloso, Gina M; Natarajan, Pradeep; et al. (JAMA Cardiol, 2024)
IMPORTANCE: Familial hypercholesterolemia (FH) is a genetic disorder that often results in severely high low-density lipoprotein cholesterol (LDL-C) and high risk of premature coronary heart disease (CHD). However, the impact of FH variants on CHD risk among individuals with moderately elevated LDL-C is not well quantified. OBJECTIVE: To assess CHD risk associated with FH variants among individuals with moderately (130-189 mg/dL) and severely (≥190 mg/dL) elevated LDL-C and to quantify excess CHD deaths attributable to FH variants in US adults. DESIGN, SETTING, AND PARTICIPANTS: A total of 21 426 individuals without preexisting CHD from 6 US cohort studies (Atherosclerosis Risk in Communities study, Coronary Artery Risk Development in Young Adults study, Cardiovascular Health Study, Framingham Heart Study Offspring cohort, Jackson Heart Study, and Multi-Ethnic Study of Atherosclerosis) were included, 63 of whom had an FH variant. Data were collected from 1971 to 2018, and the median (IQR) follow-up was 18 (13-28) years. Data were analyzed from March to May 2023. EXPOSURES: LDL-C, cumulative past LDL-C, FH variant status. MAIN OUTCOMES AND MEASURES: Cox proportional hazards models estimated associations between FH variants and incident CHD. The Cardiovascular Disease Policy Model projected excess CHD deaths associated with FH variants in US adults. RESULTS: Of the 21 426 individuals without preexisting CHD (mean [SD] age 52.1 [15.5] years; 12 041 [56.2%] female), an FH variant was found in 22 individuals with moderately elevated LDL-C (0.3%) and in 33 individuals with severely elevated LDL-C (2.5%). The adjusted hazard ratios for incident CHD comparing those with and without FH variants were 2.9 (95% CI, 1.4-6.0) and 2.6 (95% CI, 1.4-4.9) among individuals with moderately and severely elevated LDL-C, respectively. The association between FH variants and CHD was slightly attenuated when further adjusting for baseline LDL-C level, whereas the association was no longer statistically significant after adjusting for cumulative past LDL-C exposure. Among US adults 20 years and older with no history of CHD and LDL-C 130 mg/dL or higher, more than 417 000 carry an FH variant and were projected to experience more than 12 000 excess CHD deaths in those with moderately elevated LDL-C and 15 000 in those with severely elevated LDL-C compared with individuals without an FH variant. CONCLUSIONS AND RELEVANCE: In this pooled cohort study, the presence of FH variants was associated with a 2-fold higher CHD risk, even when LDL-C was only moderately elevated. The increased CHD risk appeared to be largely explained by the higher cumulative LDL-C exposure in individuals with an FH variant compared to those without. Further research is needed to assess the value of adding genetic testing to traditional phenotypic FH screening.

Plasma proteome-wide analysis of cerebral small vessel disease identifies novel biomarkers and disease pathways. - Gomez, Gabriela T; Shi, Liu; Fohner, Alison E; Chen, Jingsha; Yang, Yunju; Fornage, Myriam; Duggan, Michael R; Peng, Zhongsheng; Daya, Gulzar N; Tin, Adrienne; Schlosser, Pascal; Longstreth, W T; et al. (medRxiv, 2024)
Cerebral small vessel disease (SVD), as defined by neuroimaging characteristics such as white matter hyperintensities (WMHs), cerebral microhemorrhages (CMHs), and lacunar infarcts, is highly prevalent and has been associated with dementia risk and other clinical sequelae. Although conditions such as hypertension are known to contribute to SVD, little is known about the diverse set of subclinical biological processes and molecular mediators that may also influence the development and progression of SVD. To better understand the mechanisms underlying SVD and to identify novel SVD biomarkers, we used a large-scale proteomic platform to relate 4,877 plasma proteins to MRI-defined SVD characteristics within 1,508 participants of the Atherosclerosis Risk in Communities (ARIC) Study cohort. Our proteome-wide analysis of older adults (mean age: 76) identified 13 WMH-associated plasma proteins involved in synaptic function, endothelial integrity, and angiogenesis, two of which remained associated with late-life WMH volume when measured nearly 20 years earlier, during midlife. We replicated the relationship between 9 candidate proteins and WMH volume in one or more external cohorts; we found that 11 of the 13 proteins were associated with risk for future dementia; and we leveraged publicly available proteomic data from brain tissue to demonstrate that a subset of WMH-associated proteins was differentially expressed in the context of cerebral atherosclerosis, pathologically-defined Alzheimer's disease, and cognitive decline. Bidirectional two-sample Mendelian randomization analyses examined the causal relationships between candidate proteins and WMH volume, while pathway and network analyses identified discrete biological processes (lipid/cholesterol metabolism, NF-kB signaling, hemostasis) associated with distinct forms of SVD. Finally, we synthesized these findings to identify two plasma proteins, oligodendrocyte myelin glycoprotein (OMG) and neuronal pentraxin receptor (NPTXR), as top candidate biomarkers for elevated WMH volume and its clinical manifestations.

Sleep macro-architecture and dementia risk in adults: Meta-analysis of 5 cohorts from the Sleep and Dementia Consortium. - Yiallourou, Stephanie; Baril, Andree-Ann; Wiedner, Crystal; Misialek, Jeffrey R; Kline, Christopher E; Harrison, Stephanie; Cannon, Ethan; Yang, Qiong; Bernal, Rebecca; Bisson, Alycia; Himali, Dibya; Cavuoto, Marina; et al. (medRxiv, 2024)
STUDY OBJECTIVES: Poor sleep may play a role in the risk of dementia. However, few studies have investigated the association between polysomnography (PSG)-derived sleep architecture and dementia incidence. We examined the relationship between sleep macro-architecture and dementia incidence across five US-based cohort studies from the Sleep and Dementia Consortium (SDC). METHODS: Percent of time spent in stages of sleep (N1, N2, N3, REM sleep), wake after sleep onset and sleep maintenance efficiency were derived from a single night home-based PSG. Dementia was ascertained in each cohort using its cohort-specific criteria. Each cohort performed Cox proportional hazard regressions for each sleep exposure and incident dementia, adjusting for age, sex, body mass index, anti-depressant use, sedative use, and status. Results were then pooled in random effects meta-analyses. RESULTS: The pooled sample comprised 4,657 participants (30% women) aged ≥60 years (mean age was 74 years at sleep assessment). There were 998 (21.4%) dementia cases (median follow-up time of 5 to 19 years). Pooled effects of the five cohorts showed no association between sleep architecture and incident dementia. When meta-analyses were restricted to the three cohorts which had dementia case ascertainment based on DSM-IV/V criteria (n=2,374), higher N3% was marginally associated with an increased risk of dementia (HR: 1.06; 95%CI: 1.00-1.12, per percent increase N3, p=0.050). CONCLUSIONS: There were no consistent associations between sleep macro-architecture measured and the risk of incident dementia. Implementing more nuanced sleep metrics remains an important next step for uncovering more about sleep-dementia associations.